إحياء مصطلحات قرآنية وصوفية: دراسة التراكيب الفكرية للشيخ عبد السلام ياسين - Abdul Rahman Hussein Obeid (Universiti Sains Islam Malaysia, 2024)
Terminologies are indicators of linguistic and intellectual changes of a vocabulary in its historical context. This vocabulary may preserve some of its original meaning despite the sequential shifts, but it will get away from the lexical meaning and abbreviate intellectual, social and cultural dimensions. Sheikh Yassine is one of thinkers who took the Quranic teachings an intellectual reference. This article aims to present the educational and intellectual terminologies that Yassine developed in response to modernity and western thought. He was excessively concerned to derive those terminologies from the Quran and give them a practical dimension. The method used in this research is inductive by collecting terminologies from Yassine’s books, and subject it to the method of analysis and criticism in order to show its influence. The most important outcome of this research is the conception of qawmah (uprising) that Yassine invented is based on seven stages starting from the prophet’s revolution among his people and ended with establishing a united ummah (Islamic community). While the most firmed concept of Yassine is minhaj which become a code that actualize his project of reformation. Yassine has set some precise principles to deal the mystical experience and teachings of tasawwuf and finally he called for protecting reason from the mazes of mysticism when he dedicated his life completely to da’wah (missionary) and reformation.